Simulation analysis of acceleration and pressure response of cavity structures subjected to water-entry impact - ZHANG Yueqing; PANG Duo; CAI Weijun; LI Jianchen (Zhongguo Jianchuan Yanjiu, 2018)
[Objectives] Ship slamming, torpedo dropping and aircraft ditching will all impose great impact loads on structures. For ships, the hull structure will suffer severe impact damage which can cause subsequent adverse effects on the internal instruments and endanger the safety of the onboard crew. As such, research into water-entry impact is of great importance. [Methods] To this end, a test system is designed to conduct water-entry impact testing based on wedge and arc body models as the research objective. In the test process, accelerometers and PVDF piezoelectric sensors are applied to measure the structure pressure and impact load. Based on the constructed cavity structure and air model, the effects of impact load on acceleration and impact response are highlighted by a simulation analysis using the ALE method, and compared with the test results. [Results] It is found that the numerical results are in good agreement with the test data, which means that an airtight structure cavity has a great influence on acceleration. The effect on the arc body is more serious than that of the wedge and there is no effect on the elastic body. The shape of the structure has an important effect on water impact pressure. [Conclusions] The results of this research can provide valuable references for the design and water impact protection of water-entry structures.